Public Service Delivery Mechanism and Rural Poverty in Nepal - Koirala, Parashar (NRB Economic Review, 2005)
Nepal is a least developed country with a per capita income of $240. The population living below poverty line is 44.6%, in which the rural poverty is over and above the urban in percentage terms. In total, about 10 percent of the population live in the urban areas where the population living below the poverty line is 17.8 percent; in the remaining 90 percent residing in the rural areas, 46.6 percent of them are living below the poverty line. With regard to rural poverty, the delivery mechanism developed in rural and urban areas consists of Village Development Committee (VDC), Municipality, and District Development Committee (DDC). There is a division of work among the VDC, Municipality, DDC and the line ministries. The VDC is the lowest institution at the grass root level, which send development plan for necessary funding to DDC and the DDC to the Ministry of Local Development and to the National Planning Commission. This mechanism has been in operation for the last forty years. There has been some progress in development works such as in education, electricity, telephone, road and possession of radio. But the report and data show that the level of poverty has been increasing since FY 1976/77. To find out the impact of development activities on per capita income, a regression coefficient of each development activity has been estimated through the method of least squares. Through test statistics, it is demonstrated that there is a significant difference of the impact of independent variables (electricity, literacy, road, radio and telephone) on the dependent variable (per capita income).